EXPLORATION OF AVAILABLE OFFSITE CONSTRUCTION METHODS IN INDIAN CITIES FOR COST AND TIME SAVINGS IN HOUSING CONSTRUCTION - Myneni, Kranti Kumar; Undaru, Varsha (International Journal of Engineering Science Technologies, 2023)
Observing the current rate of growth of Indian cities and their future predictions, there is a huge demand for urban housing. India aims to achieve adequate safe and affordable housing for all by 2030 and the current shortage of dwelling units is at 20 million and rising. Achieving such huge demands in a short time using traditional construction methods have a lot of drawbacks like rise in pollution, construction waste, worker safety etc., which in turn cause hikes in cost and time of completion of a project. Offsite techniques can help mitigate or avoid a lot of these ill effects by transferring all impeding activities to a controlled environment. Here we identify the suitable and most convenient approach of construction that can be followed by comparing offsite construction with traditional construction and composite construction. Then evaluate the identified offsite building techniques available to us and, based on Cost and Time parameters to identify a most feasible solution, by tabulating the time and costs incurred. This is done by AHP analysis on basis of technical, manufacturer specifications, on- site performance and literature. Finally we can deduce the most suitable offsite technique for mass housing construction for low to medium rise construction and come to a conclusion that choosing GFRG we would reduce overall cost and time of construction on site for housing and it could help to achieve speedy and cost effective construction solution to best suit the growing needs of the urban settlements.